Association of the risk factor UNC13A with survival and upper motor neuron involvement in amyotrophic lateral sclerosis - Manini, Arianna; Casiraghi, Valeria; Brusati, Alberto; Maranzano, Alessio; Gentile, Francesco; Colombo, Eleonora; Bonetti, Ruggero; Peverelli, Silvia; Invernizzi, Sabrina; Gentilini, Davide; Messina, Stefano; Verde, Federico; et al. (Frontiers in Aging Neuroscience, 2023)
Background The UNC13A gene is an established susceptibility locus for amyotrophic lateral sclerosis (ALS) and a determinant of shorter survival after disease onset, with up to 33.0 months difference in life expectancy for carriers of the rs12608932 risk genotype. However, its overall effect on other clinical features and ALS phenotypic variability is controversial. Methods Genotype data of the UNC13A rs12608932 SNP (A–major allele; C–minor allele) was obtained from a cohort of 972 ALS patients. Demographic and clinical variables were collected, including cognitive and behavioral profiles, evaluated through the Edinburgh Cognitive and Behavioral ALS Screen (ECAS) – Italian version and the Frontal Behavioral Inventory (FBI); upper and lower motor neuron involvement, assessed by the Penn Upper Motor Neuron Score (PUMNS) and the Lower Motor Neuron Score (LMNS)/Medical Research Council (MRC) scores, respectively; the ALS Functional Rating Scale Revised (ALSFRS-R) score at evaluation and progression rate; age and site of onset; survival. The comparison between the three rs12608932 genotypes (AA, AC, CC) was performed using the additive, dominant, and recessive genetic models. Results The rs12608932 minor allele frequency was 0.31 in our ALS cohort, in comparison to 0.33–0.41 reported in other Caucasian ALS populations. Carriers of at least one minor C allele (AC+CC genotypes) had a shorter median survival than patients with the wild-type AA genotype (-11.7 months, p=0.013), even after adjusting for age and site of onset, C9orf72 mutational status and gender. Patients harboring at least one major A allele (AA+AC genotypes) and particularly those with the wild-type AA genotype showed a significantly higher PUMNS compared to CC carriers (p=0.015 and padj= 0.037, respectively), thus indicating a more severe upper motor neuron involvement. Our analysis did not detect significant associations with all the other clinical parameters considered. Conclusion Overall, our findings confirm the role of UNC13A as a determinant of survival in ALS patients and show the association of this locus also with upper motor neuron involvement.